Construction of microbial platform chassis for CO2 utilisation - Della Valle, S; Tu, W; Huang, WE (Elsevier, 2023)
To achieve a circular bioeconomy, carbon streams can be utilised through microbial conversion to produce value-added compounds. Although some microorganisms are naturally able to grow on these renewable carbon sources and generate desirable molecules, significant engineering is required to develop platform chassis exhibiting attractive performance parameters for industrial-scale processes. Here, we provide a brief overview of the core considerations in chassis engineering for autotrophic bioproduction, including carbon and energy supply, in addition to emerging standards for rewiring metabolic pathways to enhance growth and biosynthetic capabilities. We highlight examples of successful strategies, placing emphasis on recent advances in engineering autotrophic capabilities in both native autotrophs and heterotrophs.